Institutional Challenges Constraining the Performance of Agricultural Marketing Cooperative Societies (AMCOs) amid Climate Change: Insights from Coffee Farming in Nyasa District - Ndunguru, Fredy; Mbunda, Kastory; Ndunguru, Geofrey (Journal of Management Studies and Development, 2025)
This study examines the institutional challenges that constrain the performance of AMCOS in the face of climate change in Nyasa District, an emerging coffee-producing area in southern Tanzania. Employing a qualitative case study approach, data were collected through 20 semi-structured interviews and four focus group discussions with AMCOS leaders from four cooperatives, complemented by a review of relevant policy documents and operational reports. Thematic analysis revealed six interrelated institutional challenges: volatility in global coffee prices, resistance to adopting improved and climate-smart farming practices, the persistent influence of unauthorized private buyers (locally known as Kangomba), limited access to affordable financing, inadequate transportation infrastructure, and the lack of local coffee processing facilities. These challenges collectively weaken cooperative governance, erode member trust, reduce operational efficiency, and constrain the ability of AMCOS to facilitate climate-resilient agricultural development. The findings underscore the need for integrated policy and development interventions, including cooperative-friendly financing mechanisms, infrastructure investment, regulatory enforcement, and participatory extension services. Strengthening the institutional embeddedness and adaptive capacity of AMCOS is critical to improving smallholder farmer livelihoods and ensuring the long-term sustainability of the coffee sector in climate-vulnerable rural areas.